A systematic review of radiation dose associated with different generations of multidetector CT coronary angiography - Sabarudin, A.; Sun, Z.; Ng, K.H. (2012)
The purpose of this paper is to perform a systematic review on radiation dose reduction in coronary computed tomography (CT) angiography that is done using different generations of multidetector CT (MDCT) scanners ranging from four-slice to 320-slice CTs, and have different dose-saving techniques. The method followed was to search for references on coronary CT angiography (CTA) that had been published in English between 1998 and February 2011. The effective radiation dose reported in each study based on different generations of MDCT scanners was analysed and compared between the types of scanners, gender, exposure factors and scanning protocols. Sixty-six studies were eligible for inclusion in this analysis. The mean effective dose (ED) for MDCT angiography with retrospective electrocardiogram (ECG) gating without use of any dose-saving protocol was 6.0 ± 2.8, 10.4 ± 4.90 and 11.8 ± 5.9 mSv for four-slice, 16-slice and 64-slice CTs, respectively. More dose-saving strategies were applied in recent CT generations including prospective ECG-gating protocols, application of lower tube voltage and tube current modulation to achieve a noteworthy dose reduction. Prospective ECG-gating protocol was increasingly used in 64, 125, 256 and 320 slices with corresponding ED of 4.1 ± 1.7, 3.6 ± 0.4, 3.0 ± 1.9 and 7.6 ± 1.6 mSv, respectively. Lower tube voltage and tube current modulation were widely applied in 64-slice CT and resulted in significant dose reduction (P < 0.05). This analysis has shown that dose-saving strategies can substantially reduce the radiation dose in CT coronary angiography. The fact that more and more clinicians are opting for dose-saving strategies in CT coronary angiography indicates an increased awareness of risks associated with high radiation doses among them.